The use of e-cigarettes among university students in Malaysia - Sharifa Ezat Wan Puteh; Roslina Abdul Manap; Tidi Maharani Hassan; Izzah Syazwani Ahmad; Idayu Badilla Idris; Fariza Md Sham; Andrea Ban Yu Lin; Chun Ian Soo; Rashidi Mohamed Pakri Mohamed; Ahmad Irdha Mokhtar; Hazli Zakaria; Jing Lee; et al. (Tobacco Induced Diseases, 2018)
Introduction E-cigarette use is an emerging phenomenon with increasing recognition and acceptance globally. This study aims to create a profile of e-cigarette users among university students in Malaysia.